Intrinsic Mechanical Cues and Their Impact on Stem Cells and Embryogenesis - Petzold, Jonna; Gentleman, Eileen (Frontiers in Cell and Developmental Biology, 2021)
Although understanding how soluble cues direct cellular processes revolutionised the study of cell biology in the second half of the 20th century, over the last two decades, new insights into how mechanical cues similarly impact cell fate decisions has gained momentum. During development, extrinsic cues such as fluid flow, shear stress and compressive forces are essential for normal embryogenesis to proceed. Indeed, both adult and embryonic stem cells can respond to applied forces, but they can also detect intrinsic mechanical cues from their surrounding environment, such as the stiffness of the extracellular matrix, which impacts differentiation and morphogenesis. Cells can detect changes in their mechanical environment using cell surface receptors such as integrins and focal adhesions. Moreover, dynamic rearrangements of the cytoskeleton have been identified as a key means by which forces are transmitted from the extracellular matrix to the cell and vice versa. Although we have some understanding of the downstream mechanisms whereby mechanical cues are translated into changes in cell behaviour, many of the signalling pathways remain to be defined. This review discusses the importance of intrinsic mechanical cues on adult cell fate decisions, the emerging roles of cell surface mechano-sensors and the cytoskeleton in enabling cells to sense its microenvironment, and the role of intracellular signalling in translating mechanical cues into transcriptional outputs. In addition, the contribution of mechanical cues to fundamental processes during embryogenesis such as apical constriction and convergent extension is discussed. The continued development of tools to measure the biomechanical properties of soft tissues in vivo is likely to uncover currently underestimated contributions of these cues to adult stem cell fate decisions and embryogenesis, and may inform on regenerative strategies for tissue repair.